A scientometric review of research on saprolite in Brazil from 1990 to 2022 - da Silva, Luis F. V.; Pedron, Fabrício de A.; Dos Santos, Jean C. B.; Pinto, Antônio A. [UNESP]; de Azevedo, Antônio C. (My University, 2025)
The consumption of atmospheric carbon dioxide by weathering buffers the greenhouse effect on Earth on a geological timescale. This mechanism is called the silicate carbon sink (SCS). Saprolite represents part of the weathering front of the Earth’s mantle, but historically, it has not received much attention from geoscientists. On a global scale, Brazil is the largest contributor to the SCS and the fourth largest contributor to the number of saprolite publications. In this study, Brazilian scientific production on the subject from 1990 to 2022 was assessed, considering publications indexed in the Web of Science, SciELO and Scopus databases. One hundred-eighty scientific articles were retrieved. In the last decade, seven articles were published per year. Over the 32 years under consideration, the number of articles on saprolite has increased. Most of the studies were concentrated in the southeastern region of Brazil, where the state of Minas Gerais led in terms of the number of publications (28.49%). The main areas in which the articles were published were related to ecology, Earth, and marine; however, they were cited by several others, including the areas of health and politics. A comparison of the number of publications per basin and the size of the SCS showed that there were fewer studies from the Amazon Basin than from the Paraná Basin. In conclusion, the geographical frontier for the study of saprolite in the Brazilian territory is the Amazon River Basin, and the methodological frontier is related to fluid/gas dynamics and the role of microbes in weathering at depth.
Uma revisão cienciométrica da pesquisa sobre saprolito no Brasil de 1990 a 2020
Keywords: CiteSpace; isalterite; isoalterite; science mapping; visual analytics